1995
DOI: 10.1021/ja00121a036
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Catalyzed [5 + 2] Cycloadditions of Vinylcyclopropanes and Alkynes: A Homolog of the Diels-Alder Reaction for the Synthesis of Seven-Membered Rings

Abstract: The synthetic significance of the Diels-Alder cycloaddition coupled with the recognition that vinylcyclopropanes have dienelike properties has stimulated much interest over the past few decades in the development of a homolog of the Diels-Alder reaction for seven-membered-ring synthesis involving the cycloaddition of vinylcyclopropanes with -systems (Scheme 1:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
181
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 411 publications
(188 citation statements)
references
References 0 publications
1
181
0
6
Order By: Relevance
“…[5] In addition,t hey have been utilized in the industry for crude oil refining, photoconductive surfaces,d yes and pigments manufacturing and deodorants. [6] Because of these numerous applications,avariety of efficient methodologies have been developed for their synthesis.I nt his regard, the transitionmetal-catalyzed cyclization reactions represent av ery attractive alternative because simplesubstrates can be transformed into more elaborated structures under mild reactionc onditions.I n spite of these methods, the cycloaddition reactions, [7] ring expansion reactions, [8] ring-closing metathesis [9] and domino cyclization reactions [10] have emerged as powerful tools to the preparation of wide range of seven-membered carbocycles.F rom transition metals, the applicationo fi ron salts has increased in the last few years due to the lowcost, low toxicity,compatibility with solvents, air and with aw ide range of functional groups. [11] It has been shownt hat iron salts are useful to promote several transformations, such as carbon-heteroatomb ondf ormation, [12] cross-coupling reactions of Grignard reagents with organic electrophiles, [13] heteroatom-heteroatom andc arbon-carbon bond formation [14] and for the synthesis of heterocycle compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In addition,t hey have been utilized in the industry for crude oil refining, photoconductive surfaces,d yes and pigments manufacturing and deodorants. [6] Because of these numerous applications,avariety of efficient methodologies have been developed for their synthesis.I nt his regard, the transitionmetal-catalyzed cyclization reactions represent av ery attractive alternative because simplesubstrates can be transformed into more elaborated structures under mild reactionc onditions.I n spite of these methods, the cycloaddition reactions, [7] ring expansion reactions, [8] ring-closing metathesis [9] and domino cyclization reactions [10] have emerged as powerful tools to the preparation of wide range of seven-membered carbocycles.F rom transition metals, the applicationo fi ron salts has increased in the last few years due to the lowcost, low toxicity,compatibility with solvents, air and with aw ide range of functional groups. [11] It has been shownt hat iron salts are useful to promote several transformations, such as carbon-heteroatomb ondf ormation, [12] cross-coupling reactions of Grignard reagents with organic electrophiles, [13] heteroatom-heteroatom andc arbon-carbon bond formation [14] and for the synthesis of heterocycle compounds.…”
Section: Introductionmentioning
confidence: 99%
“…
Abstract: Iron-promoted cyclization of 1-benzyl-2-alkynylbenzenes with diorganyl diselenides led to the synthesiso f9 -(organoselanyl)-5H-benzo [7]annulenes whereby the mutual action between diorganyl diselenides andiron(III) chloride in a0 .5:1.0 molr atio was essential in order to achieve the maximal yields of the products.T he cyclization reaction tolerated av ariety of functional groups,s uch as trifluoromethyl, chloro,f luoroa nd methoxy,i nb otht he 1-benzyl-2-alkynylbenzenes and the diorganyl diselenides, giving the seven-membered heterocyclic products exclusively via a7-endo-dig cyclization process.
…”
mentioning
confidence: 99%
“…[12] In the light of these results and taking into account the catalytic properties (for the hydrogenation of ketones) reported in the literature for (2,2Ј-bipyridine)rhodium complexes in basic methanolic media (no activity detected under neutral conditions), [5a] the activity of the (1)rhodium Scheme 3. Proposed effect of NaOH in the catalytic site of Rhcatalyzed hydrogenation of ketones in water under hydrogen prescomplex in the reduction of acetophenone at pH ϭ 9 (by sure; S ϭ H 2 O addition of sodium hydroxide) was re-examined.…”
mentioning
confidence: 95%
“…Wender and co-workers reported that a cationic rhodium(i) complex catalyzes the [52] cycloaddition of vinylcyclopropanes with alkynes faster than a neutral rhodium complex. [6] However, in our case, the cationic rhodium complex [Rh(cod) 2 ] BF À 4 (cod 1,5-cyclooctadiene) required a longer reaction time than [RhCl(PPh 3 ) 3 ] to complete the rearrangement, although the initial reaction rate was faster (Table 1, entries 1 and 2). These reactions are the first examples of the selective rearrangement of an allenylcyclopropane into the corresponding methylenecyclopentene.…”
mentioning
confidence: 62%
“…[5] More recently the wound-healing properties of these root extracts, which had drifted into folklore, were confirmed experimentally by Papageorgiou, and the active components identified as 1, 2, and closely related derivatives. [6] These natural products exhibit many other interesting biological effects including antibacterial, [7] antifungal, [8] anti-inflammatory, [9] antitu- (1) and shikonin (2). mor, [10] analgesic, [9a,11] antipyretic, [12] and immunostimulatory [13] activities.…”
Section: Methodsmentioning
confidence: 99%